Talapotaka Pushpa: A Promising Herbal Remedy for Diabetes Mellitus - Reddy, Dr. K. R. C. (Asian Journal of Pharmaceutics (AJP), 2018)
Talapotaka is the synonym of plant Cassia auriculata in Ayurvedic classics. It is commonly known as Avartaki in Sanskrit. It carries a beautiful bright yellow-colored flower having a potent antidiabetic activity. Diabetes mellitus (DM) is associated with several changes and impairment in the function of many vital organs. Herbal remedies for DM always recover the above-mentioned complications of DM. Talapotaka Pushpa (C. auriculata flower) is one such herbal remedy which could improve DM. In the present review article, data are compiled supporting the antidiabetic potential of Talapotaka Pushpa that may be helpful for the researchers to focus on the priority areas of research yet to be discovered.